(untitled) (International Journal of Physiotherapy, 2016)
Background: Efficacy of rehabilitation program for subjects with orthosis with objective measurement. The study aiming to objectively compare the PCI and walking speed of normal children with ambulatory spastic diaplegic. Also we aimed to analyze whether BMIhad impact on energy cost. Methods: 41 normal children and 41 community walking spastic diaplegic aged between 6 to 18 yrs. were assessed to compare the PCI. Speed of walking and heart rate were checked constantlyboth barefoot and in shoes in normal children and with and without conventional AFO in children with spastic diaplegic at their chosen velocities over four consecutive lengths of a 12.5m walkway i.e. total 50m.,Pre and Post readings are taken. Heart rate is affected by speed; PCI with speed of walking and heart rate was calculated for each child. Results: The mean PCI in shoes and barefoot was same in normal children i.e. 0.05 ±0.039beats/meter. The PCI for children with pathological gait i.e. spastic diaplegic without orthosis and with orthosis is 0.199 ±0.176 and 0.104± 0.093beats/meter appreciably greater than that for normal children(p less than 0.05). Conclusion: This study showed that walking with orthosis in spastic diplegic CP children showed higher costs of energy and slower walking speed compared normal children with age matched. The PCI of walking, with orthosis in children with spastic Diplegic cerebral palsy is less as compared to without orthosis i.e. gait is more energy efficient with orthosis. BMI doesn’t show any correlation with PCI further study may require.